PENERAPAN DALAM KEBIJAKAN FIDUSIA SEBAGAI DAMPAK DIGITALISASI REVOLUSI INDUSTRI 4.0 - Adhi Budi Susilo (J-EBI: Jurnal Ekonomi Bisnis Islam, 2021)
Indonesia as a country that is in global competition seeks to build and strengthen the economy by creating a climate to make it easier to do business where the parameter of measure in the ease of doing business is one of which is the ease of obtaining a loan / credit (getting credit). In its journey as an adaptation in the digitization of the industrial revolution 4.0 in order to empower information technology resources as an information and communication system, it is necessary to implement policies which are strategic steps to anticipate changes in the global world that include digitizing the industrial revolution 4.0. The purpose of this paper is to determine the application of fiduciary policies as an impact digitalization of industrial revolution 4.0 and to find out the obstacles faced in fiduciary policies as a result of digitizing the industrial revolution 4.0 The results of the research found that the application in Fiduciary policy has accommodated the presence of digitalization of the industrial revolution 4.0 which still requires the role of the state which has a function as regulator, provider and counterweight to be able to adjusting the rules according to the development of technologyKeywords: Fiduciary Policy, Digitalization, Industrial Revolution